1996
DOI: 10.7326/0003-4819-125-12-199612150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Procedural Competence: A Prospective Study of Training in Endoscopic Retrograde Cholangiopancreatography

Abstract: At least 180 ERCPs were required before these gastroenterology fellows could be considered competent in ERCP. This number is much greater than that previously recommended, and these findings have substantial implications for training guidelines and issues of competence and certification in ERCP. The methods used to define and evaluate competence in ERCP could also be used to assess competence in other medical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
2
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(194 citation statements)
references
References 0 publications
10
173
2
6
Order By: Relevance
“…Three papers used logistic regression (9;54;56) and two papers used multiple regression (25;58) to adjust for confounding factors before testing for a relationship between experience and operation time. Generalized linear mixed models were used once (30). Multivariate techniques of either type were reported increasingly from 1996.…”
Section: Multivariate (Trend)mentioning
confidence: 99%
“…Three papers used logistic regression (9;54;56) and two papers used multiple regression (25;58) to adjust for confounding factors before testing for a relationship between experience and operation time. Generalized linear mixed models were used once (30). Multivariate techniques of either type were reported increasingly from 1996.…”
Section: Multivariate (Trend)mentioning
confidence: 99%
“…This knowledge is generally acquired in the context of a multidisciplinary hepatobiliary-pancreatic academic fellowship training program. ERCP requires significant focused training and experience to maximize success and safety (11,37). A study (22) among surgery fellows found that an average of seven months of training in ERCP was required to reach the desired success level (85% cannulation rate).…”
Section: Trainingmentioning
confidence: 99%
“…In this study, the minimum performance frequency of more than three per year was endorsed by the expert panel as the best estimate at the time of the study. Although models have been developed to predict the number of practice attempts required by a trainee to achieve clinical competence, 54 and various studies have been undertaken to define this value for specific procedures, 16,[55][56][57][58][59][60][61] the minimum frequency required to attain mastery may be specific to the procedure and to the individual learner. Published ''frequency of performance standards'' for procedural skill mastery or maintenance of competence were not found in the literature.…”
Section: Limitations and Future Questionsmentioning
confidence: 99%
“…The minimum frequency of performing or supervising a procedure to maintain competence was arbitrarily set by the investigators at three or more times per year, as suggested by the expert opinion panel and a review of the literature. 16,[54][55][56][57][58][59][60][61] A decision rule ( Fig. 2) was derived by the investigators as a tool to allow the assignment of each procedural skill to one of four training levels; 1) postgraduate certification (PG), 2) undergraduate certification (UG), 3) a skill where competency to perform was unnecessary but knowledge of the procedure was deemed important (PG knowledge only), or 4) an unnecessary skill with respect to clinical competency or acquisition of skill specific knowledge (unnecessary).…”
Section: -51mentioning
confidence: 99%